2020
DOI: 10.1002/1873-3468.13908
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analyses suggest that mucopolysaccharidosis patients may be less susceptible to COVID‐19

Abstract: We used transcriptomic (RNA-seq) analyses to determine whether patients suffering from all types and subtypes of mucopolysaccharidosis (MPS), a severe inherited metabolic disease, may be more susceptible to coronavirus disease 2019 (COVID-19). The expression levels of genes encoding proteins potentially involved in SARS-CoV-2 development were estimated in MPS cell lines. Four genes (GTF2F2, RAB18, TMEM97, PDE4DIP) coding for proteins potentially facilitating virus development were down-regulated, while two gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Almost all patients with infection reported mild, typical COVID-19 symptoms [ 21 ]. Those observations are in line with reports from other health care units worldwide [ 5 , 9 , 22 , 23 , 24 , 25 ]. Only in three cases, the worsening of primary disease symptoms was observed (two patients with NPC and one NPB: psychomotor agitation or deterioration of motor abilities), despite the continuation of symptomatic treatment during infection.…”
Section: Discussionsupporting
confidence: 92%
“…Almost all patients with infection reported mild, typical COVID-19 symptoms [ 21 ]. Those observations are in line with reports from other health care units worldwide [ 5 , 9 , 22 , 23 , 24 , 25 ]. Only in three cases, the worsening of primary disease symptoms was observed (two patients with NPC and one NPB: psychomotor agitation or deterioration of motor abilities), despite the continuation of symptomatic treatment during infection.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to the general Israeli population, the infection rate among LSDs patients is higher (4.4% based on the Israeli Ministry of Health data) but the mortality and morbidity rate is significantly lower. While this might be the result of the relatively small patient cohort, this finding may actually be supported by a study of transcriptomic analyses performed on MPS patients' cell lines by Pierzynowska et al that showed that MPS patients' cells may have lower susceptibility to infection by SARS-CoV-2 due to specific changes in expression of genes coding for proteins involved in interactions with viral proteins [ 15 ]. Another important point is the vast majority of the described Israeli cohort includes younger patients which could partially explain the mild disease, as occurs also in the general pediatric population in Israel.…”
Section: Discussionmentioning
confidence: 88%
“…Compared to the general Israeli population, the infection rate among LSDs patients is higher (4.4% based on the Israeli Ministry of Health data) but the mortality and morbidity rate is signi cantly lower. This is actually supported by a study of transcriptomic analyses performed on MPS patients' cell lines by Pierzynowska et al that showed that MPS patients' cells may have lower susceptibility to infection by SARS-CoV-2 due to speci c changes in expression of genes coding for proteins involved in interactions with viral proteins 10 . Another important point is the vast majority of the described Israeli cohort includes younger patients which could partially explain the mild disease, as occurs also in the general pediatric population in Israel.…”
Section: Discussionmentioning
confidence: 77%